(untitled) (Applied Biological Research, 2016)
To evaluate the efficacy of silver nitrate and various carbon sources on callus induction and regeneration, four maize varieties of Bangladesh viz., ‘Barnali’, ‘Mohar’, ‘Shuvra’ and ‘Khoi bhutta’ were evaluated. Four carbon sources either singly or in combination forming seven treatments were tested. The highest callusing (67.1%) was recorded in treatment wherein 2.0% sucrose was used for ‘Mohar’. Study on the impact of seven different doses of AgNO3 revealed approximately 1.5- fold higher callus induction in ‘Mohar’ when 9 mg Ladded to N6 medium. For regeneration, 3-4 weeks transferred to plant regeneration medium where IAA 0.5 mg L-1 + BAP 1.0 mg L-1 were used. Of the four genotypes, ‘Mohar’ showed highest regeneration (62.1%) in MS medium. Maximum shoot elongation and well-developed root formation were observed in ‘Mohar’ (15.75 cm) and ‘Khoi bhutta’ (82.2%), respectively. Higher doses of AgNO3 were found effective in callus induction. Analysis of variance showed significant differences in genotypes with respect to callusing and regeneration efficiency.